Transformasi Teknologi Dalam Birokrasi: Analisis Dampak Digitalisasi Terhadap Efisiensi Birokrasi - Hikmah Muhaimin; Dian Wijaya; Anindiya Liliani Wijanarko; Ayunda Eka Permata (Jurnal Ilmu Pemerintahan, 2025)
As technology advances over time, this study seeks to examine the influence of digitalisation on the efficiency of bureaucratic processes. It also explores the challenges encountered during the transition to a digital bureaucracy, including disparities in access to technology, resistance to change, and concerns regarding data security. By leveraging information and communication technology, digitalisation has revolutionised the traditionally slow and paper-dependent bureaucracy into a more efficient, transparent, and accessible system. This study adopts a qualitative methodology, analysing pertinent literature, relevant policies, and applicable government institutions to thoroughly assess the impact of digitisation within public sector organisations